(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine whether there is an effect of arm power training on the ability of upper service in volleyball games in extracurricular students of the Palu Christian Salvation Army Middle School. The problem in this study is: Is there an effect of arm power training on the ability of the upper limb service? This study uses a quantitative approach, involving extracurricular students of the Palu Christian Salvation Army Middle School as the population, and 20 students as samples using total sampling. This data collection technique was carried out by providing service treatment for the initial test and final test to students who were in the sample. The results of this study indicate that the average value before being given arm power training was 8.25, and after being given arm power training, 13.55, so that there was an increase of 5.3. Based on the results of the test sample calculation where t count = 12.33 while t table at the 5% level with degrees of freedom (db) = n-1 = 19 is 1.729 so it can be concluded that Ho is rejected and Ha is accepted because the t count value is greater than t table, which is 12.33> 1.729. The results of the study indicate that there is an effect of arm power training on the ability of upper service in volleyball games in extracurricular students of the Palu Salvation Army Christian Middle School. Arm power training can be used as an alternative exercise that can increase arm muscle strength, increase endurance, and increase upper body stability.